Can Serum Histone H4 Level Be a Biomarker in Ulcerative Colitis? - , İrfan Küçük and , Fatih Özçelik and , Yusuf Yazgan and , İsmail Yılmaz and , Mustafa Kaplan and , İdris Yıldırım (Turkish Journal of Gastroenterology 1, 2024)
Background/Aims: Histones are a part of neutrophil extracellular trap molecules which were reported to have diagnostic values in some inflammatory diseases. We aimed to evaluate whether serum histone H4 can be a diagnostic and prognostic marker for ulcerative colitis. Materials and Methods: This case–control study included 58 ulcerative colitis patients (34 males and 24 females) and 45 healthy controls (25 males and 20 females). The Mayo clinical scoring system was used for the clinical and endoscopic features. Truelove–Witt’s method was applied to the histology activity index. The human histone H4 kit was used for the enzyme-linked immunosorbent assay of serum histone H4. Results: Serum histone H4 was significantly lower in the ulcerative colitis group compared to the control groups [268 (14-1639) vs. 598 (310-2134) ng/L, P < .001, respectively]. Among the ulcerative colitis patients, there was no correlation between serum histone H4 and disease extent, Mayo clinical scoring, Mayo endoscopic activity subscoring, histology activity index, inflammatory markers, d-dimer, and leukocyte and neutrophil counts (r < 0.20, P > .05). Histone H4 levels were not statistically significant between the patients with no medication and those taking 5-aminosalicylate and/or other agents (P > .05). The receiver operating characteristic curve analysis revealed that serum histone H4 concentrations had a 0.782 (95%CI: 0.690-0.857, P < .001) diagnostic accuracy for ulcerative colitis. The specificity and sensitivity for the cutoff level of ≤364 ng/L were 88.9% and 72.4%, respectively. Conclusion: Decreased serum histone H4 values may be used as an auxiliary marker in the progression and diagnosis of ulcerative colitis. Further studies are needed to delineate this relationship between clinical and laboratory traits of ulcerative colitis and serum histone H4. Cite this article as: Küçük İ, Özçelik F, Yazgan Y, Yılmaz İ, Kaplan M, Yıldırım İ. Can serum histone H4 level be a biomarker in ulcerative colitis? Turk J Gastroenterol. 2024;35(1):4-10.